Enhancing Online Shopping: Factors Influencing Repurchase Intentions Among University Students - Manafe, Leonard Adrie; Puspitasari, Fanny Dwi; Fatchurrohman, Mochamad (FEB - Universitas Lampung, 2025)
This study examines the relationships among perceived ease of use, perceived usefulness, user satisfaction, and repurchase intention among Management students at Mahardhika College of Economics. Employing a quantitative approach supported by structural equation modeling, the analysis reveals that both perceived ease of use and perceived usefulness significantly and positively influence user satisfaction. Furthermore, satisfaction mediates the relationship between usability perceptions and repurchase intention, highlighting its central role in shaping behavioral outcomes. These findings suggest that platform designers should simultaneously enhance interface simplicity and communicate functional value to foster genuine user loyalty. The results provide practical implications for website developers, product managers, and brand strategists aiming to strengthen user engagement in an increasingly competitive digital marketplace. Future research is encouraged to incorporate psychological factors, demographic characteristics, and situational variables to enrich the theoretical understanding of digital consumer behavior and provide a more comprehensive model of online loyalty formation.